STUDI KADAR TANIN DAN INHIBISI OKSIDAN HASIL MASERASI BIJI PINANG WANGI DENGAN PERLAKUAN DAN TANPA PERLAKUAN ULTRASONIK - Rosalina; Hibrah; Agung Kurnia Yahya; Ferry Ikhsandy (JURNAL TEKNOLOGI PERTANIAN, 2022)
Areca nut from Padang Pariaman as an export commodity is rich in tannin content and its ability as an antioxidant is used as the object of this research. The extraction of fragrant betel nut seeds has been carried out using the usual kinetic maceration method and the kinetic maceration method with ultrasonic wave irradiation pretreatment. The purpose of this study was to study the effect of ultrasonic irradiation on the tannin content, total phenol and antioxidant inhibition of the ethanol extract of areca nut seeds. A total of 20 grams of areca nut powder in a mesh variation of 20, 40 and 70 was extracted in 200 ml of ethanol with a solvent variation of 65% and 80%. Using three treatments, namely maceration treatment without ultrasonic irradiation, maceration with 15 minutes of ultrasonic irradiation pretreatment and the third treatment with 30 minutes of ultrasonic irradiation. The solvent was evaporated in a rotary evaporator and then tested for tannin levels using Follin Denish and DPPH reagents to measure antioxidants. The results of the highest tannin content were obtained in the third treatment, namely maceration with ultrasonic irradiation treatment 30 minutes, areca nut powder size 40 mesh, ethanol solvent 80% obtained tannin content of 12.5%. Meanwhile, the highest antioxidant activity was obtained at 70 mesh size, 80% ethanol solvent and the same treatment, which was 81.78.